Diabetes care provision and glycaemic control in Northern Ireland: a UK regional audit. Issue 5 (25th April 2005) - Cardwell, C R; Patterson, C C; Allen, M; Carson, D J
Abstract : Aims: To assess the care received, compared to national guidelines, and to investigate factors associated with glycaemic control in children and adolescents with type 1 diabetes attending clinics in Northern Ireland. Methods: An audit of the care provided to all patients attending 11 paediatric diabetes clinics commenced in 2002. A research nurse interviewed 914 patients completing a questionnaire recording characteristics, social circumstances, and aspects of diabetes management, including the monitoring of complications and access to members of the diabetes team. Glycaemic control was measured by glycosylated haemoglobin (HbA1c ), determined at a DCCT aligned central laboratory. Results: The average HbA1c concentration was 8.8% (SD 1.5%), with 20% of patients achieving recommended HbA1c levels of less than 7.5%. In the year prior to the audit, 76% of patients were reviewed by a diabetes specialist nurse and 42% were tested for microalbuminuria. After adjustment for confounding factors, better glycaemic control was identified, particularly in patients who had attended exactly four diabetes clinics in the previous year, were members of the patient association Diabetes UK, and lived with both natural parents. Conclusions: In Northern Ireland only a minority of patients achieved recommended HbA1c levels. Furthermore, children and adolescents with diabetes were reviewed by fewer specialists and were less intensively monitored for microvascular complications than recommended. There was evidence of better control in children who were members of Diabetes UK, suggesting that parental attitude and involvement could lead to benefits.